2018
DOI: 10.1139/cjas-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness and sensory attributes of 11 muscles from carcasses within the Canadian cull cow grades

Abstract: The eating quality and shear force of meat from mature beef carcasses graded within the Canadian grading system were compared with youthful carcasses. Eleven muscles were obtained from mature-graded carcasses with >50% ossification (D1, D2, D3, and D4; n = 84) and youthful carcasses with <50% ossification [over 30 mo (OTM); n = 18, and under 30 mo (UTM) of age; n = 18, based on dentition]; muscles were aged 14 d prior to sensory and shear force analysis. Many muscles from mature-graded carcasses were jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In general, most literature supports that total collagen content would be mostly similar between animal maturities (Couvreur et al, 2019;Dos Santos Fontes et al, 2021;Lucero-Borja et al, 2014;Patten et al, 2008), although collagen solubility would decrease with increasing age (Alvarenga et al, 2021;Dos Santos Fontes et al, 2021;Gredell et al, 2018). A greater amount of perceptible connective tissue in cooked beef from mature carcasses has also been consistently reported (Jurie et al, 2007;Lucero-Borja et al, 2014;Roberts et al, 2017). Between beef and dairy type cull cows, total and insoluble collagen contents would be similar (Jurie et al, 2007).…”
Section: Factors Influencing Tenderness Of Mature Beefmentioning
confidence: 87%
See 2 more Smart Citations
“…In general, most literature supports that total collagen content would be mostly similar between animal maturities (Couvreur et al, 2019;Dos Santos Fontes et al, 2021;Lucero-Borja et al, 2014;Patten et al, 2008), although collagen solubility would decrease with increasing age (Alvarenga et al, 2021;Dos Santos Fontes et al, 2021;Gredell et al, 2018). A greater amount of perceptible connective tissue in cooked beef from mature carcasses has also been consistently reported (Jurie et al, 2007;Lucero-Borja et al, 2014;Roberts et al, 2017). Between beef and dairy type cull cows, total and insoluble collagen contents would be similar (Jurie et al, 2007).…”
Section: Factors Influencing Tenderness Of Mature Beefmentioning
confidence: 87%
“…This deficiency in tenderness of mature beef is often highly noticeable in more inherently tough cuts from the chuck and round primals. The study by Roberts et al (2017) reported poorer initial and overall tenderness scores, greater perceptible connective tissue, and higher shear force values in the semimembranosus, biceps femoris, semitendinosus, triceps brachii , and others from carcasses classified as mature by the Canadian grading system relative to those under 30 months of age. In general, the poor tenderness of mature beef relative to youthful carcasses is dependent on the individual cut, where the differences may be less apparent in certain inherently tender muscles such as the psoas major, infraspinatus, and longissimus lumborum ( Alvarenga et al, 2021 ; Roberts et al, 2017 ; Stelzleni et al, 2007 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation